2014
DOI: 10.1038/ncomms5284
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous piezoelectricity in two-dimensional graphene nitride nanosheets

Abstract: Piezoelectricity is a unique property of materials that permits the conversion of mechanical stimuli into electrical and vice versa. On the basis of crystal symmetry considerations, pristine carbon nitride (C 3 N 4 ) in its various forms is non-piezoelectric. Here we find clear evidence via piezoresponse force microscopy and quantum mechanical calculations that both atomically thin and layered graphitic carbon nitride, or graphene nitride, nanosheets exhibit anomalous piezoelectricity. Insights from ab inito c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(179 citation statements)
references
References 22 publications
6
170
1
2
Order By: Relevance
“…Benefitting from its ultrathin and easily bendable structure, the graphene membrane presents an ultrahigh direct piezoelectric coefficient (~37 nC N − 1 , approximately two orders of magnitude higher than traditional piezoelectric materials and functional graphene [16][17] ), although the converse piezoelectric coefficient is small (~12.5 μm V − 1 ) due to graphene's semi-metallic property and large quantum capacitance.…”
Section: Piezoelectric Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefitting from its ultrathin and easily bendable structure, the graphene membrane presents an ultrahigh direct piezoelectric coefficient (~37 nC N − 1 , approximately two orders of magnitude higher than traditional piezoelectric materials and functional graphene [16][17] ), although the converse piezoelectric coefficient is small (~12.5 μm V − 1 ) due to graphene's semi-metallic property and large quantum capacitance.…”
Section: Piezoelectric Coefficientmentioning
confidence: 99%
“…15 Achievement of piezoelectricity in previous pioneering works requires the functionalization or nanopatterning of graphene to break this centrosymmetry. 16,17 Furthermore, in its intrinsic (semi-)metallic states, graphene is clearly non-piezoelectric and/or non-flexoelectric. 17 In addition, its singleatom thickness leads to an ill-defined out-of plane strain gradient and a questionable breakage of the centrosymmetric flexoeletricity.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated vertical piezocoefficient was found to be about 1.4 nm/V, which is much higher than that of conventional piezoelectric materials [135]. Atomically-thin graphene nitride also exhibits anomalous piezoelectricity, due to the fact that a stable phase of a sheet features regularly spaced triangular holes, as indicated by ab initio calculations [136]. Directional dependent piezoelectric effects in chemical vapor deposited MoS 2 monolayers were measured through lateral PFM when an electric field was applied laterally across the flakes [131].…”
Section: Strain Engineering and Piezoresponse Force Microscopymentioning
confidence: 84%
“…Previously, we have experimentally shown that vertically aligned CNTs exhibit a memristive switching associated with their strain and polarization [1][2][3]. Analysis of the literature [4][5][6] has shown that non-uniform strain in carbon nanostructures can lead to the appearance of a piezoelectric effect and the corresponding internal electric field in them. We put forward a proposal that the non-uniform strain of the CNT acts as an additional source of resistance which depends on the value of the current flowing.…”
Section: Introductionmentioning
confidence: 99%